2009
DOI: 10.1016/j.ultsonch.2009.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Minimising oil droplet size using ultrasonic emulsification

Abstract: The efficient production of nanoemulsions, with oil droplet sizes of less than 100nm would facilitate the inclusion of oil soluble bio-active agents into a range of water based foods. Small droplet sizes lead to transparent emulsions so that product appearance is not altered by the addition of an oil phase. In this paper, we demonstrate that it is possible to create remarkably small transparent O/W nanoemulsions with average diameters as low as 40nm from sunflower oil. This is achieved using ultrasound or high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
269
1
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 552 publications
(286 citation statements)
references
References 30 publications
(50 reference statements)
10
269
1
6
Order By: Relevance
“…When sonication amplitude increased from 60%-100%, there is a reduction of droplet size from 136.1 ± 2.5 nm to 108.6 ± 0.4 nm due to cavitation ( Figure 1). The intensity of cavitation activity in emulsifying tocols is proportional to sonication amplitude (Leong et al, 2009). Emulsions sonicated at three different amplitudes showed that mean droplet diameter decreases with sonication time.…”
Section: Effect Of Amplitude and Duration Of Sonication On Particle Smentioning
confidence: 97%
“…When sonication amplitude increased from 60%-100%, there is a reduction of droplet size from 136.1 ± 2.5 nm to 108.6 ± 0.4 nm due to cavitation ( Figure 1). The intensity of cavitation activity in emulsifying tocols is proportional to sonication amplitude (Leong et al, 2009). Emulsions sonicated at three different amplitudes showed that mean droplet diameter decreases with sonication time.…”
Section: Effect Of Amplitude and Duration Of Sonication On Particle Smentioning
confidence: 97%
“…The processes of deformation and fragmentation of the dispersed phase have been considered in [21][22][23][24][25][26][27][28][29][30] but these processes are still not fully understood and require large energy consumptions for their practical realization.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The R-P equation [2] is modified by introducing the acoustic radiation factor by Prospertti A., but these are the motions of tiny bubbles in the liquid. In the real life, the two-phase system of liquid-liquid two-phase system or membrane isolation under ultrasonic action is often encountered, such as: ultrasonic catalytic emulsification system [3], ultrasound in the life of the cell membrane in the transport of substances and energy transmission [4], how the ultrasound effect of soft matter droplets (such as: gels, vesicles, etc.) will be change?…”
Section: Introductionmentioning
confidence: 99%